(-)-glaciantarcin, a new dipeptide and some secondary metabolites from the psychrophilic yeast Glaciozyma antarctica PI12 - Andi R. Rosandy,; Yeoh, Chian Ying; Cheah, Yoke Kqueen; Seng, Joe Lim; Jalifah Latip,; Abdul Munir Abd. Murad,; Muntaz Abu Bakar,; Rozida Mohd. Khalid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A new dipeptide, (-)-glaciantarcin (1) and three known compounds, cyclo(-Pro-Gly) (2), 1-(2-deoxypentofuranosyl)-5-methyl-2,4(1H,3H)-pyrimidinedione (3) and vidarabine (Ara-A) (4), were isolated from Glaciozyma antarctica PI12, a cold-adapted yeast. The chemical structures were elucidated by FT-IR, NMR and mass spectrometry. The cytotoxicity and antioxidant activities of compounds 1-4 were evaluated by using the MTT bioassay on MCF-7 (human breast cancer cell line), PC-3 (human prostate cancer cell line) and HEK-293 (normal human embryonic kidney cell line) and DPPH free radical scavenging activity, respectively. At concentration of 400 μM, all compounds showed the highest activity on MCF-7, with compound 1 at 65%, compound 2 (70%), compound 3 (66%) and compound 4 (58%) cell viability. All compounds exhibited weak antioxidant properties. To the best of our knowledge, this is the first report of compounds 1-4 from Glaciozyma antactica.